PERSPEKTIF KONSERVASI ARSITEKTURAL PADA MASYARAKAT JAWA - Johannes Adiyanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2015)
Title: Architectural Conservation Perspective In Javanese Community Traditionally, Indonesian, with tropical climate, use wooden material for their building. The consequences of that material and the tropical climate is building cannot durable compare stone material. The building needs renewal more frequently and sometimes reconstruction.This study focus in Java building (houses) and their culture. In Javanese manuscripts (primbon), repairing the house is the same level with build the new one. To repair or to build the house for Javanese is not only the technical aspect (like structure or the form), but also about the connection with nature and their expectation in the future. Based on that understanding what the meaning of the conservation in Javanese culture? The subject for this study is architectural Javanese manuscripts (Primbon, Kawruh Kalang, and Kawruh Griya). This study uses hermeneutics method by Paul Ricouer. There are three steps: step one is to build the conservation understanding in Javanese culture, using content analysis. Step two is validation. This step using Ngibikan Village for case study. Step three is discussion. This step exploring the philosophical aspect in Javanese culture and compare with Ricouer thinking about „history,memory and forgetting?. The result of this exploration studies that for Javanese culture, conservation not only discuss about building. Based on Javanese philosophy that live only „stop? for drink (urip mung mampir ngombe), the conservation is a process, not result; the conservation is dynamic or change, not permanent or unchanged.